Ricardo Palma and Catholic culture - Gonzales Alvarado, Osmar (2020)
The purpose of this article is to describe the relationships that Ricardo Palma had with Catholicism. In ideological terms, he was a convinced liberal and, in that sense, a critic of religious institutions. However, it is necessary to establish a distinction: Palma understood very well the importance of the religious attitude, which he represented in his famous Peruvian Traditions; and simultaneously he was a persistently and staunchly anticlerical, criticizing and mocking religious ideas and practices.